Sexismo em jogo: uma análise sobre o preconceito e o assédio sofrido por mulheres gamers - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2018)
This work consists of a qualitative and quantitative study of sexism in digital games taking into account the point of view of women victims of this type of violence. The objective is to understand the facets of this phenomenon, as this is a fundamental requirement for creating strategies to combat prejudice and harassment against women in this space. For this, in addition to the bibliographic review on the subject, we undertook image analysis, questionnaire application and structured interview. An online questionnaire was released during 7 days (04/02/2018 to 04/09/2018).The same had the participation of 213 players aged between 12 and more than 30 years and revealed that the games are part of the routine of the participants, since 76.5% of them play daily, despite this, more than half of them have experienced some episode of prejudice, harassment and offenses where their gender was a determining factor. This first phase also demonstrated that these episodes are experienced at an average frequency for 40% of them, 37% reported low frequency, however this number drops significantly if we consider that 17% of them attributed this low frequency to the use of mechanisms to avoid these episodes misogynist In addition, even those who have not suffered violence because of their gender know women who have been through it. In the second stage of the research, 10 players were interviewed among those who affirmed in the first phase to have suffered gender bias in the gamer universe, the participants answered a questionnaire with 9 open questions about the theme. At this stage it was evident the negative influence that these episodes of violence exert on the players, resulting in difficulty of concentration, withdrawal from games, feelings of fear, humiliation and incapacity among others. In addition, they all feel that their gender directly influences how they are assessed within games. Because of the violence suffered, many seek ways to avoid going through this, seeking, among other strategies, make use of names, photos and words that conceal their gender and play only with friends. Among the interviewees 9 feel safer playing with friends and have stopped playing some game because there is someone to accompany them. In the face of these sexist episodes, some question the macho nature of the offenses and denounce the player who had the toxic behavior, while others ignore the offenses and leave the game temporarily or permanently because they feel incapable. When questioned about what led to this type of behavior of the aggressor and how this reality could be modified the players responded that what leads to this behavior exceeds the gamer universe itself, although it strengthens these behaviors when not properly reprimand . Despite this, they believe that this scenario can be modified provided there is greater support for women in the sector, investment in awareness campaigns and more appropriate punishment measures and recognize that in addition to measures in the gamer universe, changes in society as a whole are fundamental.
Keywords: Jogos digitais; Violência de gênero; Indústria dos jogos; Mulheres gamers - Preconceito; Mulheres gamers - Assédio; Sexismo em jogo; CNPQ::CIENCIAS SOCIAIS APLICADAS